Perceived dental needs and barriers to utilization of dental services among elders in India - A cross-sectional survey - N G Bhuvaneshwari; G V Usha; Nagesh Lakshminarayan (Wolters Kluwer Medknow Publications, 2021)
Background: The population of geriatric patients in India is increasing, and the uneven geographic distribution of dentists and the various age-related factors are likely to pose an oral health challenge in the near future. Aim: The aim of this study was to assess perceived needs and identify and describe the barriers associated with oral health service utilization among the elderly population aged 65-74 years in Davangere city. Methodology: A cross-sectional door-to-door survey using a self-designed, structured, validated questionnaire was carried out with a sample of 1440 elders. They were randomly selected through multistage sampling technique. Information regarding demographic details, systemic conditions, oral hygiene practices, perceived need, utilization rate of dental services, and factors acting as barriers for the utilization of dental services among the elderly were collected. Chi-square test and Pearson correlation were applied. Results: About 70.5% of the subjects had utilized the dental services in their lifetime, but only 41.4% had utilized in the previous year. Fifty percent of the elders perceived a problem in their oral cavity. Most of our respondents suffered from more than one chronic disease and had utilized the dental services. The cost of treatment, nonsuitability of location of clinic, indirect cost due to transport, the appointment system, and no availability of services on weekends acted as the important barriers to utilize the dental services. Conclusion: Financial constraint and lack of perceiving dental problems as severe acted as major barriers. Preventive oral hygiene measures tailored to meet the unique needs of the individual patient are essential.